Structural response of a concrete cable-stayed bridge under thermal loads. (1st December 2018) - Sousa Tomé, Emanuel; Pimentel, Mário; Figueiras, Joaquim
Highlights: Structural response of cable-stayed bridges to temperature and long-term effects. A methodology for analysis of the structural response of bridges under thermal loads. Optimal deployment location of temperature sensors. 17 months of continuous experimental data. Abstract: Daily and seasonal temperature variations have a significant influence on the structural response of bridges, inducing strains, displacements or rotations of the same order of magnitude, or even larger, than those due to dead or live loads. Besides understanding the structural behaviour under the operational loads, the characterization of the structural response induced by the daily and seasonal temperature variations is mandatory for the critical assessment of the bridge structural condition and when proactive conservation is envisaged. In this study, a methodology is proposed for the simulation of the structural response of large concrete bridges under the effects of realistic temperature variations, aiming at the optimum compromise between accuracy and simplicity of the involved procedures. The transient temperature field in a set of representative cross-sections is obtained from the available meteorological data via two-dimensional thermal analyses. The temperature field is decomposed into uniform, linear and non-linear components, the former two being introduced in a mechanical model of the bridge to obtain the transient structural response. The methodology is applied to a concrete cable-stayed bridge equipped with a permanent structural monitoring system. The measured and calculated hourly temperatures, deflections, bearing displacements, rotations and stay-cable forces are compared during a period of 17 months and good agreement is generally found. The consideration of the radiative cooling effects is demonstrated to be essential in other to obtain a good estimation of the thermal field of the bridge. The behaviour of the bridge is discussed and the relative contribution of each temperature component to a given structural response is disclosed. A discussion on the optimal deployment location of a minimum set of embedded temperature sensors in order achieve the best estimators of the temperature components (uniform and linear) is also presented.